Paraguay : Third Review Under the Stand-By Arrangement, Request for Extension of the Arrangement, and Request for Waivers of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
The staff paper for the Third Review Under the Stand-By Arrangement on Paraguay focuses on the macroeconomic framework and medium-term scenario, risks, and capacity to repay the IMF. There have been delays in implementing some structural measures, especially related to the approval of banking legislation, owing to a shift in the political environment and congressional delays. Macroeconomic performance has been better than envisaged under the program. The authorities have adopted a new strategy involving a two-stage approach that they believe is politically feasible to achieve but will require more time to implement.